Geopolitical Rivalries: The Ethnic Dimensions and Global Implications of the Russia-Ukraine Conflict - Ovuede, David Obukokhwo; Okpevra, Uwomano Benjamin; Ovuede, David Lenin (ARISTO, 2026)
This paper investigates the Russia-Ukraine conflict as a nexus of historical legacies, ethnic nationalism, and US-Russia geopolitical contestation, rooted in the aftermath of the Soviet Union’s dissolution. By synthesising historical analysis, policy documents, through a mixed-methods framework, the study positions the war as a proxy struggle shaped by competing globalist and irredentist agendas. Four interconnected drivers emerge: Russia’s resurgence as a counterweight to US-led unipolarity; NATO’s eastward expansion as a catalyst for Russian security anxieties; energy geopolitics influencing regional dependencies; and de-Russification policies amplifying ethnic tensions in Ukraine’s divided sociopolitical landscape. The findings revealed the conflict transcends Ukraine’s sovereignty, reflecting broader systemic rivalries where external powers exploit historical grievances – such as Soviet-era identity fractures and contested territorial narratives – to advance strategic aims. These dynamics have entrenched Ukraine as a battleground for ideological and resource dominance, fuelling ultranationalism and internal discord. The analysis highlights the interplay between structural forces– great-power competition, alliance militarisation – and localised factors, including memory politics and economic disparities, which collectively hinder diplomatic resolution. The study critiques the humanitarian consequences of proxy warfare, particularly civilian displacement and infrastructural collapse. It further underscores the role of digital disinformation and economic sanctions as hybrid tools of modern conflict. Keywords: Russia-Ukraine Conflict; Geopolitical Rivalry; Ethnic Nationalism; Globalism; NATO